Analisis Pengaruh Market Share Perbankan Syariah terhadap Pertumbuhan Ekonomi Indonesia (Studi Tren: 2015-2024) - Fitra Dila Lestari Fitra; Siti Fatimah Zahra Siti Fatimah Zahra; Lathiefah Rabbaniyah Lathiefah Rabbaniyah (Journal of Islamic Business Management Studies (JIBMS), 2026)
Indonesia holds significant potential in the development of Islamic banking; however, its market share had only reached 7.44% as of September 2024  far below the 15% target set by Bank Indonesia. Meanwhile, national economic growth has remained stagnant at around 5% over the past decade. This study aims to examine the effect of Islamic banking market share on Indonesia's economic growth over the period 2015–2024. The method employed is simple linear regression based on secondary time series data sourced from OJK and BPS, with Shapiro-Wilk normality testing, Durbin-Watson autocorrelation testing, and coefficient of determination analysis using SPSS 26. The findings indicate that Islamic banking market share has no significant effect on economic growth (sig. = 0.789 > 0.05), with an R² value of only 0.9%. This study contributes to strengthening the empirical evidence that the scale of Indonesia's Islamic banking sector remains too limited to meaningfully drive economic growth, while also serving as a basis for recommending that regulators accelerate the expansion of the Islamic finance industry through more aggressive and innovative policies.